2010
DOI: 10.4314/jasem.v14i1.56475
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Erythrocyte Sedimentation Rate (ESR) Using Trisodium Citrate, Normal Saline and Whole Blood in Ethylene Di Amine Tetra Acetic Acid (EDTA)

Abstract: Erythrocyte sedimentation rate (ESR) was carried out on 200 apparently healthy individuals (131 males and 69 females) in Ekpoma using trisodium citrate, normal saline diluents and whole blood suspension in EDTA without any diluents. The Westergren method was adopted for this study as recommended by the International Committee for Standardization in Haematology (ICSH). The tests were read at 30 minutes and 1 hour intervals and results recorded as mm in 30mins and mm in 1hr respectively. The Mean ± SD of ESR val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 5 publications
0
4
1
Order By: Relevance
“…In addition to this, the mean ± SD ESR values of males were less than that of females which contradicts this finding. This may due to the fact that most of our male study participants were old aged and had a history of tuberculosis (23). However, the result of our study was found to be in contrary with an earlier report conducted in India, which stated that the ESR measurement values of Citrated blood was greater by 4-6 mm/hr than EDTA (7).…”
Section: Discussioncontrasting
confidence: 99%
“…In addition to this, the mean ± SD ESR values of males were less than that of females which contradicts this finding. This may due to the fact that most of our male study participants were old aged and had a history of tuberculosis (23). However, the result of our study was found to be in contrary with an earlier report conducted in India, which stated that the ESR measurement values of Citrated blood was greater by 4-6 mm/hr than EDTA (7).…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, the mean ± SD ESR values of males were less than those of females, contradicting the finding. This might be due to the fact that most of our male participants were old and had history of TB [31].…”
Section: Discussionmentioning
confidence: 99%
“…A total of 70 participants were recruited for this comparative cross-sectional study. The double population mean formula was used to calculate the required sample size using the mean and standard deviation (SD) of TSC and EDTA taken from other studies [31] with 80% power (0.84) and 95% level of significance (1.96).…”
Section: Sample Size Determinationmentioning
confidence: 99%
“…In addition to this, the mean ± SD ESR values of males were less than that of females which contradicts this finding. This may due to the fact that most of our male study participants were old aged and had a history of tuberculosis (30).…”
Section: Discussionmentioning
confidence: 99%
“…A total of 70 study participants were recruited for this comparative cross-sectional study. A double population mean formula was used to calculate the required sample size using mean of citrate and EDTA taken from standard deviation and mean difference are taken from other studies (30) hours in accordance with the recommendation of ICSH (29). We filled the Westergren tube exactly to "0"mark and place the tube in the rack for 1 hour and the ESR results were recorded in mm/h.…”
Section: Sample Size Determinationmentioning
confidence: 99%